Blood Type Approach in Integrated Social Studies Learning: Innovating Personalized Learning Strategies to Improve Students' Social-Emotional Intelligence - Purnomo, Dian; Aramudin (Global Action and Education for Society, 2026)
Social-emotional intelligence (KSE) is an important aspect of student development, which supports academic success and social interaction. The blood type approach, which focuses on individual characteristics, can be used to improve students' KSE in Integrated Social Studies learning. This study aims to examine the application of the blood type approach in Integrated Social Studies learning as an innovative strategy to develop students' KSE. The method used is a qualitative approach with a case study design, involving classroom observation, interviews with teachers and students, and analysis of learning documents. The results showed that the application of the blood type approach improved social interaction, group cooperation, and students' ability to manage their emotions. Students feel more connected to the learning material, while teachers can adjust learning strategies according to the social-emotional characteristics of the students. This approach also helps to increase a sense of empathy between students of different blood types. In conclusion, the blood type approach in Integrated Social Studies learning has been shown to be effective in improving students' social-emotional intelligence, with a positive impact on their social and emotional abilities in the context of learning and daily life.